GAMBARAN HISTOLOGIS PULMO MENCIT JANTAN (Mus musculus L.) SETELAH DIPAPARI ASAP ROKOK ELEKTRIK - Nanin Triana; Syafruddin Ilyas; Salomo Hutahaean (Saintia Biologi, 2013)
The effects of electric cigarette exposure on lung tissue of mice were studied. The experiments using completely randomized design (CRD) with 3 treatments, i.e.  treatment of electric cigarette with strawberry flavour, tobacco flavour, and control treatment that was not exposed by cigarette smoke. Eight male mice were used for each group. Exposure treatment was done every day for 2 consecutive weeks with dosage 20 times suction using syringe of 60 mL. After receiving treatment for 2 weeks, the mice were killed by cervical dislocation. The lungs were isolated and prepared histologically using paraffin method and then stained with by haematoxylin and eosin  (HE). The results showed that, smoke treatment mice lose weight significantly (p< 0.05). In gross anatomy, electric cigarrete smoke affect lung feature, but histological observation on  membrane damage, damage to the lumen and the relationship between alveoli the smoke effect were statistically unsignificant (p>0.05).. In summary short period exposure to electric  cigarette smoke  tends affect lung damage in anatomy, but statistically has no effect of the damage to the lung tissue.   Keywords: alveolar lumen, alveolar membrane, electric cigarettes